Regulation of microRNA expression in the neuronal stem cell niches during aging of the short-lived annual fish Nothobranchius furzeri - Terzibasi Tozzini, Eva; Savino, Aurora; Ripa, Roberto; Battistoni, Giorgia; Baumgart, Mario; Cellerino, Alessandro (Frontiers in Cellular Neuroscience, 2014)
In the last decade, our group has intensively studied the annual fish Nothobranchius furzeri as a new experimental model in Biology specifically applied to aging research. We previously studied adult neuronal stem cells of N. furzeri in vivo and we demonstrated an age-dependent decay in adult neurogenesis. More recently we identified and quantified the expression of miRNAs in the brain of N. furzeri and we detected 165 conserved miRNAs and found that brain aging in Nothobranchius furzeri is associated with coherent up-regulation of well-known tumor suppressor miRNAs, as well as down-regulation of well-known onco miRNAs - In the present work we we characterized the expression of miR-15a, miR-20a and microRNA cluster 17~92 in the principal neurogenetic niches of the brain of young and old subjects of Nothobranchius furzeri, by using in situ hybridization techniques, together with PCNA immuno-staining for a simultaneous visualization of the neuronal progenitors - We found that: 1) the expression of miR-15a is higher in the brain of old subjects and concentrates mainly in the principal neurogenetic niches of telencephalon and optic tectum, 2) the expression of miR-20a is higher in the brain of young subjects, but more widespread to the areas surrounding the neurogenic niches, 3) finally, the expression of the microRNA cluster 17~92 is higher in the brain of young subjects, concentrated mainly in the principal neurogenic niches of telencephalon and cerebellum, and with reduced intensity in the optic tectum. Taken together, our data show that these microRNAs, originally identified in whole-brain analysis, are specifically regulated in the stem cell niche during aging.